Digital Persona vs Real Person: A Study on The Attractiveness of Human and Virtual Influencers in Social Media Advertising - Reynaldi Dwi Junianta; Masyithoh Annisaush Sholihah; Binarin Tirto Andika; Dwi Martutiningrum; Muhammad Saddam Sofyandi (PT SOLUSI EDUKASI BERDIKARI, 2024)
This study aims to compare the differences in the attractiveness of product advertising content with human influencers and VTubers using the audience experience approach. The audience's experience is seen through an assessment of the pragmatic and hedonic qualities of the two advertisements viewed. Attrakdiff is used as a method to measure the assessment of both product advertisements. There are 20 respondents who are asked to view both advertisements and fill out two different questionnaires representing advertisements with human influencers and VTubers. The results show that the attractiveness of advertisements with human influencers and VTubers has almost the same attractiveness. There are differences in pragmatic and hedonic-identity quality (human influencers are superior) and hedonic-stimulation (VTubers are superior), which differentiate between the two. Although there are differences in the assessment of the audience's experience in watching content from human influencers and VTubers, both still have almost the same appeal.